1998
DOI: 10.1096/fasebj.12.1.119
|View full text |Cite
|
Sign up to set email alerts
|

Vasoactive intestinal peptide enhancement of antigen-induced differentiation of a cultured line of mouse thymocytes

Abstract: The prominence of vasoactive intestinal peptide (VIP) in rodent thymic neurons suggested that this potent mediator of T cell functions may alter developmental responses of thymocytes to T cell receptor (TCR) -dependent stimulation. CD4+8+ DPK cells derived from a thymic lymphoma of a TCR transgenic mouse respond to pigeon cytochrome C (PCC) antigen in association with distinct I-E MHC II haplotypes on antigen-presenting cells (APCs) by differentiating into CD4+8- T cells. The specific recognition of VIP by two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 35 publications
2
25
0
Order By: Relevance
“…For example, two studies using Balb/c mouse thymocyte subsets disagreed on the VPAC1:VPAC2 ratios in DN and SP8 thymocyte subsets. In contrast, their data did agree with respect to DP and SP4 subsets that showed higher VPAC2 vs VPAC1 mRNA levels [57,59] . These discrepancies can most likely be attributed to PCR primers used and/or experimental conditions such as media culture conditions.…”
Section: Vpac Receptor Expression Profile During Thymocyte Developmentmentioning
confidence: 80%
See 1 more Smart Citation
“…For example, two studies using Balb/c mouse thymocyte subsets disagreed on the VPAC1:VPAC2 ratios in DN and SP8 thymocyte subsets. In contrast, their data did agree with respect to DP and SP4 subsets that showed higher VPAC2 vs VPAC1 mRNA levels [57,59] . These discrepancies can most likely be attributed to PCR primers used and/or experimental conditions such as media culture conditions.…”
Section: Vpac Receptor Expression Profile During Thymocyte Developmentmentioning
confidence: 80%
“…This idea is supported by the VPAC2 transgenic mouse model where forcing the expression of VPAC2 in a C57BL/6 Th1 skewed this mouse strain towards a Th2 phenotype [61] (see below). Functionally, two reports have shown evidence that VPAC2 mediates IL-2 suppression upon TCR activation in DP cells, and that VPAC2 signaling enhances DP →SP4 differentiation without altering apoptosis, viability, proliferation or cell numbers [57,59] . A third study revealed that VPAC1 signaling was contributing to the protection of spontaneous and glucocorticoid-induced apoptosis [62] .…”
Section: Vpac Receptor Expression Profile During Thymocyte Developmentmentioning
confidence: 99%
“…In murine thymocytes, initial studies suggest that murine thymocytes express VIP receptors, although there is no agreement on the number of binding sites due to different experimental procedures. Although thymocytes have relatively few binding sites as compared with purified T cells (Ottaway and Greenberg, 1984;Nguyen et al, 1987), functional receptors were identified on Tcell lymphomas of thymic origin , whereas VPAC 1 and VPAC 2 mRNA expression has been reported in different sets of mouse native thymocytes and in an immature T-cell line from a spontaneous thymic lymphoma (Pankhaniya et al, 1998). In rat thymocytes, flow cytometry analysis demonstrates a predominant expression of VPAC 2 and a more restricted pattern in the expression of VPAC 1 (Delgado et al, 1999c).…”
Section: B Biochemical Pharmacological and Signaling Key Features mentioning
confidence: 99%
“…In rat thymocytes, flow cytometry analysis demonstrates a predominant expression of VPAC 2 and a more restricted pattern in the expression of VPAC 1 (Delgado et al, 1999c). Although it is clear that VIP affects several aspects of thymus biology such as cytokine production, apoptosis, differentiation, and mobility through direct effects on T cells (Ernstrom et al, 1995;Delgado et al, 1996a;Xin et al, 1997;Jiang et al, 1998;Pankhaniya et al, 1998), few data are available concerning the contextual role of epithelial VPAC receptors in thymus (Head et al, 1998;Reubi et al, 1998;Marie et al, 1999).…”
Section: B Biochemical Pharmacological and Signaling Key Features mentioning
confidence: 99%
“…T cells were washed with PBS ϩϩ and metallically tagged with anti-PE microbeads, followed by isolation of IL-4-positive cells using magnetic column chromatography (Miltenyi Biotec). IL-4-secreting cells eluted from the columns were counted microscopically, and their T cell composition was analyzed by flow cytometry (11). Gates were set on live lymphocytes, determined by forward and side scatter and exclusion of propidium iodide (0.5 mg/ml).…”
Section: Enumeration Of Il-4-secreting Cd4 T Cells By Cell Surface Camentioning
confidence: 99%